Multi‐Scale Geomagnetic Forcing Derived From High‐Resolution Observations and Their Impacts on the Upper Atmosphere - Cheng Sheng; Yue Deng; William A. Bristow; Yukitoshi Nishimura; Roderick A. Heelis; Christine Gabrielse (Space Weather)
Abstract Techniques developed in the past few years enable the derivation of high‐resolution regional ion convection and particle precipitation patterns from the Super Dual Auroral Radar Network (SuperDARN) and Time History of Events and Macroscale Interactions during Substorms All‐Sky Imager (ASI) observations, respectively. For the first time in this study, a global ionosphere‐thermosphere model (GITM) is driven by such high‐resolution patterns to simulate the I‐T response to the multi‐scale geomagnetic forcing during a real event. Specifically, GITM simulations have been conducted for the 26 March 2014 event with different ways to specify the high‐latitude forcing, including empirical models, high‐resolution SuperDARN convection patterns, and high‐resolution ASI particle precipitation maps. Multi‐scale ion convection forcing estimated from high‐resolution SuperDARN observations is found to have a very strong meso‐scale component. Multi‐scale convection forcing increases the regional Joule heating (integrated over the high‐resolution SuperDARN observation domain) by ∼30% on average, which is mostly contributed by the meso‐scale component. Meso‐scale electron precipitation derived from ASI measurements contributes on average about 30% to the total electron energy flux, and its impact on the I‐T system is comparable to the meso‐scale convection forcing estimated from SuperDARN observations. Both meso‐scale convection and precipitation forcing are found to enhance ionospheric and thermospheric disturbances with prominent structures and magnitudes of a few tens of meters per second in the horizontal neutral winds at 270 km and a few percent in the neutral density at 400 km through comparisons between simulations driven by the original and smoothed high‐resolution forcing patterns.